The study of features and prospects of the insurance medicine in Ukraine in modern conditions - Danylchenko, Liliya (ScienceRise: Medical Science, 2017)
Introduction. The necessity of development and incipience of insurance medicine in today's realities of Ukrainian health care system is caused by the need in qualified medical care for different groups of population depending on their material prosperity, especially for socially disadvantaged people, in stable healthcare financing, and maintaining of the proper level of medical care. The main task is the study of the modern tendencies of development and predicting of future changes in economic and social environment, as well as their influence on healthcare system. The modern development of social insurance in Ukraine confidently shows that the use of nothing but administrative measures is not enough for adequate work efficiency and reforms. Statement of research. In fact, there are a number of modern works in the national scientific literature devoted to attempts to consider the theoretical, historical, financial, economic, organizational and administrative aspects of health insurance, but comprehensive analysis of this issue still needs attention of scientists and society in general. This concept allows designing reasonable and substantiated recommendations for health insurance development. Aim: the study of features and prospects of the insurance medicine system in modern Ukrainian realities. Results and discussion. The choice of heath care model should completely meet the modern requirements in the country. The transition to health insurance should be performed considering the population’s wealth level, and possibilities of payment of part of medical services while maintaining the appropriate social protection for disadvantaged populations. Implementation of mandatory insurance is usually accompanied by the insured attachment to a particular territory which the insurance institution serves; also it should determine the procedure for transfer submission to the certain areas to equalize the financial capacity of the different regions. The existing legislation should provide a certain level of heath care services profitability, and competition in the medical services market will improve the quality of medical care. In future, it should slowly increase health care costs by financing from many different sources, and medical and diagnostic processes management using standards will make clinical management system closer to self-regulating system. Conclusion. Improvement of medical care for persons involved in one or another type of medical insurance by implementation of medical insurance system as an independent commodity and market relations in health care area is the main goal for the current health system in Ukraine